Implementation and first report of the Brazilian Kidney Biopsy Registry - Irene L. Noronha; Rodrigo José Ramalho; Claudia Maria Costa de Oliveira; Marilia Bahiense-Oliveira; Fabricio Augusto Marques Barbosa; Jose de Resende Barros Neto; Ronny Mitsuoka; Osvaldo Merege Vieira-Neto; Precil Diego Miranda de Menezes Neves (PLoS ONE, 2025)
Background Kidney biopsy registries are valuable tools for guiding clinical practice and developing health policies. In 2021, the Brazilian Society of Nephrology (SBN) created the Brazilian Kidney Biopsy Registry (BKBR). This is the first BKBR report, presenting patient data from 2021. Methods BKBR is a web-based platform hosted on the BSN website, which contains patient demographics, clinical data, frequency, and distribution of histologic diagnosis of Brazilian adult native kidney biopsies. Results Of the 1012 cases registered in 2021, 954 cases were evaluated after excluding pediatric and kidney transplant cases. Twenty-one centers enrolled patients, with representation from all Brazilian regions. There was a slight predominance of females (52.6%), a mean age of 44.7 ± 16 years, and 13.6% of patients were >65 years old. The main indication for kidney biopsy was renal dysfunction (56%) and nephrotic syndrome (41.4%), respectively. At the time of the biopsy, 47.9% of the patients were hypertensive and 15.2% were diabetic. Although 66.2% of patients had eGFR ≤60ml/min/1.73m2 upon biopsy, the majority (60.2%) had mild interstitial fibrosis and tubular atrophy. The most frequent diagnosis in the BKBR was glomerular disease (74.8%). Lupus nephritis was the most frequent diagnosis of glomerular disease (22.6%), followed by IgA nephropathy (13%) and focal segmental glomerulosclerosis (12.2%). Conclusion This is the first report of a Nationwide registry of kidney biopsies in Brazil. This data provides pivotal information about the kidney disease profile in this country with continental dimensions.